Potential anti-icing applications of encapsulated phase change material–embedded coatings; a review. (October 2020) - Azimi Yancheshme, Amir; Allahdini, Anahita; Maghsoudi, Khosrow; Jafari, Reza; Momen, Gelareh
Highlights: Potential application of EPCM embedded coatings for anti-icing purposes are assessed. EPCMs with near-above zero melting temperature, high values of latent heat and uniform size distributions are promising. Surface protrusions caused by EPCM can affect both ice formation and adhesion. Produced shear force at the ice-surface interface by volume change of EPCM can reduce ice adhesion. Released latent heat by phase change of EPCM can contribute in both ice formation and adhesion. Abstract: Icephobic surfaces are highly sought-after materials as there is a need to reduce the catastrophic outcomes of ice formation on outdoor surfaces. Existing anti-icing strategies, including superhydrophobic surfaces (SHPSs) and slippery liquid–infused porous surfaces (SLIPS), are often ineffective against frost formation or have a limited durability. As such, new approaches are required, and the incorporation of phase change materials (PCMs) into polymeric matrices offers a potential means of delaying ice formation and reducing ice adhesion on exposed surfaces. Homogeneously dispersed encapsulated PCMs (EPCMs) of uniform size inside a binder can release high amounts of latent heat and produce local shear stresses on surfaces—due to their volume change—during icing conditions, thereby reducing ice adhesion strength. Furthermore, surface protrusions produced by the EPCMs can also impart hydrophobicity or even superhydophobicity onto a surface to delay ice formation. This contribution reviews recent progress in the development of ECPM-based anti-icing surfaces. We also discuss the advantages and challenges of using PCM materials for anti-icing applications, summarize existing encapsulation methods, and outline the ECPM-based mechanisms that hinder ice formation and lower ice adhesion. Graphical abstract: Image, graphical abstract